2007
DOI: 10.1371/journal.ppat.0030084
|View full text |Cite
|
Sign up to set email alerts
|

Twin RNA Polymerase–Associated Proteins Control Virulence Gene Expression in Francisella tularensis

Abstract: The MglA protein is the only known regulator of virulence gene expression in Francisella tularensis, yet it is unclear how it functions. F. tularensis also contains an MglA-like protein called SspA. Here, we show that MglA and SspA cooperate with one another to control virulence gene expression in F. tularensis. Using a directed proteomic approach, we show that both MglA and SspA associate with RNA polymerase (RNAP) in F. tularensis, and that SspA is required for MglA to associate with RNAP. Furthermore, bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
256
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(270 citation statements)
references
References 33 publications
13
256
1
Order By: Relevance
“…Stress-induced (p)ppGpp production in Helicobacter pylori is required for survival during acid exposure and aerobic shock (Mouery et al, 2006;Wells & Gaynor, 2006), conditions typically encountered during the course of infection. In Francisella, intracellular replication and virulence are dependent on MglA and SspA, which regulates the FPI (Guina et al, 2007;Nano & Schmerk, 2007;Charity et al, 2007). In this study, we have identified a global regulatory system that plays a role in F. novicida virulence, where a relA mutant had reduced survival in macrophage-like cells, and was attenuated more than 100-fold in a BALB/c mouse model.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Stress-induced (p)ppGpp production in Helicobacter pylori is required for survival during acid exposure and aerobic shock (Mouery et al, 2006;Wells & Gaynor, 2006), conditions typically encountered during the course of infection. In Francisella, intracellular replication and virulence are dependent on MglA and SspA, which regulates the FPI (Guina et al, 2007;Nano & Schmerk, 2007;Charity et al, 2007). In this study, we have identified a global regulatory system that plays a role in F. novicida virulence, where a relA mutant had reduced survival in macrophage-like cells, and was attenuated more than 100-fold in a BALB/c mouse model.…”
Section: Discussionmentioning
confidence: 94%
“…Disruption of many of the genes in the FPI, such as iglA, iglC, pdpA and pdpD, results in attenuation in vitro or in vivo (Baron & Nano, 1998;Golovliov et al, 2003;Gray et al, 2002;Lauriano et al, 2004;Lindgren et al, 2004;Nano et al, 2004). Genes of the FPI have been shown to be regulated by MglA, encoded by mglA (Lauriano et al, 2004), and SspA, encoded by sspA (Charity et al, 2007). MglA and MglB are essential for intracellular replication and virulence in mice (Baron & Nano, 1998;Lauriano et al, 2004), and share homology with the Escherichia coli SspA and SspB proteins, which are regulators of stationary phase transcription and are involved in stress survival (Williams et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…As reported by Charity et al (2007), the F. tularensis genome contains two genes, designated rpoA1 (FTL_0261) and rpoA2 (FTL_0616), which encode two different a subunits of RNAP that differ from one another in regions that are predicted to be critical for dimer formation, promoter recognition, and activator interaction. FTL_1744 and FTL_1743 (rpoB and rpoC) encode the b and b9 subunits, respectively, and FTL_1533 (rpoZ) the v subunit.…”
Section: Identification Of a Functional Rpoh Gene Of F Tularensis Lvsmentioning
confidence: 96%
“…Overnight cultures were diluted in fresh LB medium supplemented with antibiotics and 0.5 mM IPTG and grown to OD 600 0.5-0.6 and assayed for β-galactosidase activity [9]. As a negative control, E. coli KDZif1ΔZ were cotransformed by empty pACTR-Ap-Zif and pBRGP-ω plasmids; and as a positive control by plasmids pACTR-Ap-MglA-Zif and pBGRP-SspA-ω [15]. The empty plasmid pBRGP-ω together with FTS_1067-Zif was used as another negative control.…”
Section: B2h and β-Galactosidase Assaysmentioning
confidence: 99%